PENGEMBANGAN MEDIA POBUNDO UNTUK MENANAMKAN KEMAMPUAN KOGNITIF IPS SISWA KELAS 4 SD MUHAMMADIYAH 16 SEMARANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research begins from the results of a preliminary study which shows that the social studies learning process is still dominated by lecture methods and conventional media, so that students are less focused, less motivated, and have difficulties in understanding cultural diversity material. Therefore, learning media that is interactive, interesting, and in accordance with the stage of cognitive development of elementary school students is needed. This research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, grade IV teachers, and 20 grade IV students of SD Muhammadiyah 16 Semarang. Data was collected through observation, interviews, validation questionnaires, response questionnaires, and cognitive ability tests. The research instrument used the Likert scale to assess the feasibility of media as well as measure the improvement of students' cognitive abilities. The results of the validation of material experts showed a feasibility percentage of 88.3%, 98.3%, and 91.6% with the very feasible category. Media expert validation obtained a percentage of 95% with a very feasible category. The implementation in the classroom shows that students are very enthusiastic and interested in using Pobundo Media. The results of the response questionnaire showed that this media had a high level of acceptance from students and teachers. In addition, the cognitive ability test showed an increase in students' understanding after using Pobundo Media in social studies learning. Based on the results of the research, it can be concluded that Pobundo Media is feasible, valid, and effective to be used as a social studies learning medium, especially cultural diversity materials. This media is able to increase learning motivation, help students understand concepts concretely, and improve the cognitive abilities of fourth grade students of SD Muhammadiyah 16 Semarang. Pobundo Media is recommended as an innovative visual learning media alternative in supporting the social studies learning process in elementary schools. The conclusion of this study is that Pobundo Media based on concrete media is valid, acceptable in learning to instill the cognitive abilities of social studies students in grade 4 on Cultural Diversity material in Indonesia.